2016
DOI: 10.1007/s12664-016-0694-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of delayed gastric emptying among Indian patients with long-standing type 2 diabetes mellitus

Abstract: Presence and severity of symptoms of gastroparesis did not predict delayed GE. Delayed GE, irrespective of symptoms, was associated with microvascular and macrovascular diabetic complications and increased risk of hypoglycemic episodes. HbA and BMI were independent predictors of delayed GE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
0
23
1
1
Order By: Relevance
“…Although this amount was less than our results, it should be considered that in their study gastric emptying half time has been used for the evaluation of gastroparesis (10). Anudeep et al (12) evaluated the prevalence and predictors of delayed gastric emptying among 140 patients with type 2 diabetes mellitus in which delayed gastric emptying was detected in about 29 % (40/140) of type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this amount was less than our results, it should be considered that in their study gastric emptying half time has been used for the evaluation of gastroparesis (10). Anudeep et al (12) evaluated the prevalence and predictors of delayed gastric emptying among 140 patients with type 2 diabetes mellitus in which delayed gastric emptying was detected in about 29 % (40/140) of type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on radionuclide scintigraphy results on gastric emptying in diabetic patients, the prevalence of delayed gastric emptying has been reported as 25-55% and 30% in patients with type 1 and 2 diabetes, respectively (10,11,12). Also, it has been determined that 29% of patients with gastroparesis had diabetes mellitus (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of gastric emptying in the pathogenesis of symptoms of suggestive of gastroparesis has been controversial, with some studies suggesting an association between delayed gastric emptying and upper symptoms (Table 2) [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], while others not demonstrating an association (Table 3) [59][60][61][62][63][64]. A large single-center study with 1499 patients undergoing GES for clinical evaluation found 629 (42%) patients to have delayed 4 h gastric emptying [65].…”
Section: Role Of Gastric Emptying In Symptoms Of Gastroparesismentioning
confidence: 99%
“…Amongst patients with symptoms suggestive of Gp, a considerable proportion have normal gastric emptying [6]. The majority of these patients with symptoms but normal gastric emptying are diagnosed with the Rome diagnoses of functional dyspepsia or chronic nausea and vomiting syndrome, or the GpCRC term of Chronic Unexplained Nausea and Vomiting [6,61]. Assessment of gastric emptying may have important therapeutic implications in patients with symptoms of dyspepsia.…”
Section: Role Of Gastric Emptying In Symptoms Of Gastroparesismentioning
confidence: 99%